2016
DOI: 10.1136/bjsports-2016-095999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on C reactive protein: a systematic review and meta-analysis of randomised and non-randomised controlled trials

Abstract: These results suggest that engaging in exercise training is associated with a decrease in CRP levels regardless of the age or sex of the individual; however, greater improvements in CRP level occur with a decrease in BMI or %Fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
135
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 123 publications
19
135
3
3
Order By: Relevance
“…A number of intervention studies have shown the effect of physical activity on improving biomarkers of inflammation and insulin . These intervention studies support the causal relationship between physical activity and the biomarkers, supporting the basis of our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A number of intervention studies have shown the effect of physical activity on improving biomarkers of inflammation and insulin . These intervention studies support the causal relationship between physical activity and the biomarkers, supporting the basis of our study.…”
Section: Discussionsupporting
confidence: 88%
“…However, the influence of specific components of physical activity (e.g., volume, intensity and type) on these biomarkers remains unclear . Moreover, the majority of previous studies were small and restricted to unhealthy populations with diseases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with knee OA have higher levels of circulating cartilage‐derived biomarkers compared to healthy controls . Systematic reviews that included overweight and normal‐weight youth and adult participants, with or without cardiovascular diseases , have shown a beneficial effect of exercise on reducing the C‐reactive protein (CRP) level, a molecular biomarker related to systemic inflammation also involved in OA progression. In the OA population, individual studies indicate that single bouts of exercise therapy promote immediate changes to molecular biomarkers related to cartilage extracellular matrix turnover (e.g., cartilage oligomeric matrix protein [COMP]) and inflammation (e.g., interleukin‐10 [IL‐10]) that, in general, return to baseline levels after a short period of rest .…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that physical activity interventions, including aerobic exercise and strength training, can reduce markers of peripheral inflammation. One recent review of 83 randomized and non‐randomized trials found an overall reduction in CRP following physical activity, albeit with a small effect size (Fedewa, Hathaway, & Ward‐Ritacco, ). Other reviews have demonstrated similar effects of exercise within specific patient populations such as breast cancer survivors (Meneses‐Echavez et al, ), patients with type 2 diabetes (Hayashino et al, ), and older adults (Sardeli et al, ).…”
Section: Healthy Behaviors and The Neuro‐immune Networkmentioning
confidence: 99%